Effects of boron doping and pre-heat treatment on the stabilization of tetragonal zirconia in sol-gel-derived ZrO2-SiO2 glass-ceramics - Celik, Yusuf; Buluc, Ahmet Furkan; Turan, Servet; Ersundu, Ali Ercin; Ersundu, Miray Celikbilek (SPRINGER, 2026)
The long-term performance of zirconia-based glass-ceramics in structural applications, such as restorative dentistry, depends on phase stability, controlled microstructure, and optimized mechanical properties. This study systematically examines the effects of boron doping and pre-heat treatment on the phase evolution, microstructure, and hardness of sol-gel-derived ZrO2-SiO2 glass-ceramics. Xerogel powders containing boron (1-4 mol%) were pre-treated at 650-1000 degrees C and consolidated by spark plasma sintering. Boron addition promoted tetragonal ZrO2 stabilization, while pre-heat treatment enabled controlled crystallization and grain growth. The 2 mol% boron-doped sample showed the highest hardness (7.88 GPa), similar to 6% higher than the undoped composition at 900 degrees C. Excessive boron addition at higher temperatures slightly reduced hardness due to lower density. Moderate boron doping effectively stabilizes tetragonal zirconia and tailors microstructure through a simple, scalable, and cost-efficient route, offering a promising strategy for high-performance zirconia-based glass-ceramics in structural and dental applications.
Keywords: MICROSTRUCTURE; ZRO2; TRANSFORMATION; TRANSITION; STABILITY; EVOLUTION; Materials Science